E4206: AMG 706 and Octreotide in Patients with Low‐Grade Neuroendocrine Tumors. (31st May 2018) - Lubner, Sam; Feng, Yang; Mulcahy, Mary; O'Dwyer, Peter; Giang, Guang‐Yu; Hinshaw, J. Louis; Deming, Dustin; Klein, Leonard; Teitelbaum, Ursina; Payne, Jennifer; Engstrom, Paul; Stella, Philip; et al.
Abstract: Lessons Learned: Rate of progression‐free survival at a particular point in time, i.e., a landmark analysis, is a difficult endpoint for a heterogenous malignancy such as neuroendocrine cancer. Landmark analyses can also be complicated by evolution in the standard of care during the conduct of a clinical trial. Improvements in biomarker development would be useful in developing future clinical trials in NET to better tailor individualized therapies and assess for possible efficacy endpoints. Background: Neuroendocrine tumors (NETs) are rare malignancies of the gastrointestinal (GI) tract that are highly vascularized and overexpress vascular‐endothelial growth factor (VEGF). Sunitinib has demonstrated efficacy in the pancreatic subset of NET. This study explored the activity of another oral VEGF inhibitor, AMG 706 or motesanib, a multikinase inhibitor that targets receptor tyrosine kinases, including VEGFR1, VEGFR2, VEGFR3, KIT, RET, and PDGFR (IC50s = 2, 3, 6, 8, 59, and 84 nM, respectively). Methods: This was a single‐arm, first‐line, phase II study run through the Eastern Cooperative Oncology Group. Patients with low‐grade NET (as defined by central confirmation of Ki‐67 of 0%–2%) were administered a flat dose of 125 mg per day orally combined with octreotide long acting‐repeatable (LAR) for patients who had been on a stable dose. The primary objective was to determine the 4‐month progression‐free survival (PFS). Results: Forty‐four patients were evaluated per protocol. The 4‐month PFS was 78.5%. The partial response rate was 13.6% (6/44), stable disease was 54.5% (24/44), 9.1% (4/44) had progressive disease, and 10/44 were not evaluable for response. Common toxicities included fatigue, hypertension, nausea, and headache, and most were grade 1–2. Median PFS was 8.7 months, and overall survival was 27.5 months. Conclusion: Motesanib (AMG 706) demonstrated a 4‐month PFS that met the per‐protocol definition of efficacy. Fatigue and hypertension were the most common toxicities, and few grade 3–4 toxicities were encountered. The progression‐free survival of 8.7 months in all NETs merits further study.